2012
DOI: 10.1590/s0102-311x2012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, stigma, and AIDS: a review of academic literature produced in Brazil (2005-2010)

Abstract: Given the implications of stigma for HIV/AIDS prevention and control of the epidemic, as emphasized by UNAIDS, this study analyzes theBrazilian academic production on health, AIDS, stigma, and discrimination, available This study aims to analyze the Brazilian academic literature on AIDS, stigma, and discrimination available in the SciELO database from 2005 to 2010, with the purpose of encouraging the development of research and policies on the theme in the public health field in Brazil. The review's premise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
1
11
0
5
Order By: Relevance
“…These findings are in accordance with those in other studies, which suggest there is discrimination when seropositivity is diagnosed, inducing the patient to look for access and treatment in health units that are further from the household 37,38 . Differences regarding the access and the stigma coming from the HIV infection are probable sources of bias in epidemiological analyses, because the notification depends on the proper investigation of the case.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with those in other studies, which suggest there is discrimination when seropositivity is diagnosed, inducing the patient to look for access and treatment in health units that are further from the household 37,38 . Differences regarding the access and the stigma coming from the HIV infection are probable sources of bias in epidemiological analyses, because the notification depends on the proper investigation of the case.…”
Section: Discussionsupporting
confidence: 92%
“…7 Still in this context, because of its initial association with socially deviant behaviors-which could be condemned by society-contamination by the virus caused an additional problem not only for HIV-positive individuals but also for their family members. Publically announcing that there was an infected family member, especially for mothers, became one of the dilemmas that some families experienced in regard to the HIV-positive status of their children.…”
Section: Some Mothers Didn't Want Other People In the Family To Know mentioning
confidence: 99%
“…These groups were strongly stigmatized for their behaviors, which were not accepted by society at the time. 7 Therefore, studying, searching the past, particularly the memories of health workers, in order to better understand their care methods and their feelings when facing the emergence of AIDS, enables us to consider their cultural, moral, and social conditionings and to assess them critically to avoid prejudiced attitudes, thus establishing an ethical relationship. Within this context and considering the exposed theme, the aim of this study was to describe and understand the feelings reported by health workers when facing the emergence of AIDS in a reference hospital for infectious diseases in the period 1986 to 2006.…”
Section: Introductionmentioning
confidence: 99%
“…19 Consequently, the stigmatized way people with HIV/AIDS were labeled during the epidemic was drastically minimized, although this is still not fully resolved. 20 In contrast, the lack of fear of the disease and somehow its very demystification might have passed on to the exacerbation of confidence and sense of invulnerability by the young, causing the trivialization of AIDS. Therefore, despite the implementation of public health policies, mainly aimed at the prevention of STDs among the youth audience, they mostly did not experience the drama at the beginning of the epidemic, the stigma for those infected and the experience of prejudice directed at people with the disease.…”
Section: ] (E2)mentioning
confidence: 99%